Port-city mobility challenges in Ho Chi Minh City: cruise tourism infrastructure, stakeholder governance, and sustainable urban transitions - Tran, Trong Thanh; Nguyen, Phuoc Hien; Mohamad, Bahtiar; Nguyen, Thi Kim Thoai; Nguyen, Thi Lan Chi; Le, The Hien (Frontiers in Sustainable Cities, 2025)
This study addresses the underexplored area of cruise tourism competitiveness in emerging Asian cities, focusing on port-city mobility and governance in Ho Chi Minh City (HCMC), Vietnam. Using qualitative analysis of 20 semi-structured interviews with key stakeholders, including tour operators, port authorities, and government officials, the research identifies a systemic framework of eight interdependent dimensions critical to HCMC's competitiveness: accessibility, shore excursion logistics, service quality, tourist spending behavior, cultural-commercial integration, institutional coordination, destination image, and regional integration. Findings reveal that despite HCMC's strategic location and rich cultural assets, disjointed transportation infrastructure—characterized by inefficient diesel-dependent port transfers, limited EV adoption, and poor last-mile connectivity—undermines sustainable development and visitor experiences. To address these gaps, the study proposes an integrated management framework that emphasizes mobility innovation, enhanced stakeholder collaboration, and curated cultural offerings near ports. By bridging infrastructure, governance, and cultural resource gaps, this research contributes to destination competitiveness theory for emerging Asian cruise markets and supports sustainable urban transitions by advancing SDG 11 (Sustainable Cities and Communities) through inclusive mobility planning and SDG 13 (Climate Action) by promoting low-carbon port-city transport solutions.